(untitled) (International Journal of Engineering and Computer Science, 2017)
Effects of surface and subsurface moisture on highway pavement failure in Ado-Afao Ekiti road were evaluated to determine the major causes of the deterioration of the pavement. Samples of soil were collected at five different locations along along Ado-Afao Ekiti road and the following geotechnical tests were conducted on the samples; sieve analysis, permeability, compaction, CBR, Triaxial and Atterberg limits. The results showed that the soils have liquid limit ranging from 15.8% - 17.6%, are non-plastic, linear shrinkage ranging from 0% to 3%, maximum dry density ranging from 3180g/cc to 3448 g/cc, optimum moisture content ranging from 8.2 to 9.2%, cohesion ranging from 9g/cc to 50g/cc, angle of friction ranging from 80 to 130, CBR value from 10.6 to 30.2, coarse material ranging from 65.1% to 69.9% while the fine material ranging from 30.1% to 34.9% and the permeability ranging from 3.69x10-2 x 5.8710-2m/s. All the soils are classified as organic silt of medium compressibility containing less plasticity according to Casangrade and A-2-6 (silty soil) of fair to poor rating in terms of possible use as subgrade material according to AASHTO classification. The CBR values of all samples of the soil are low compared to the standard value of 80. The permeability of the soil is high, therefore, the soil is unsuitable for road construction. The strength of the soil will further be reduced when there is rise in the level of water table and this can cause failure of the pavement upon the application of pressure